Pasts, Presents and Futures of Public Service Media: The Challenges of Adaptation and Change in the Age of Data - Głowacki, Michał (Communication Today, 2020)
Public service media have been slow to adapt to the digital age typified by the growing role of high technologies and communications services driven by databases and fed by data. Public service media corporations established in the pre-Internet era have found it difficult to approach adaptation and change both from the dynamics of the media markets and organisational perspectives. This study argues that current challenges faced by public service media are an ongoing interplay between the futures and legacy of 20th century success. Through 150 semi-structured interviews conducted in 10 cities – 6 in Europe, 3 in the USA and 1 in Canada – the study aims to investigate key path-dependencies and potential models to move public service media forwards. The struggle between the old and the new is examined through the lenses of media change, regulation and organisational cultures.